STUDI LITERATUR: STRATEGI PEMBELAJARAN BAHASA INDONESIA BERBASIS LITERASI VISUAL DALAM MENGATASI KRISIS MINAT BACA SISWA SEKOLAH DASAR - Ayumawarsih, Rika; Retno Winarni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to examine how visual literacy strategies to overcome the crisis of reading interest and reading skills of elementary school students. This research uses a Narrative Literature Review (NLR) approach to analyse various studies that discuss visual literacy and its impact on students' interest in reading in primary schools. He research findings show that visual literacy is very effective in Indonesian language learning, especially in overcoming the reading interest crisis that is commonly found in primary schools. The implementation of visual literacy allows students to learn more interactively, exploratively, and collaboratively, which in turn increases the overall effectiveness of learning. This research suggests that the implementation of visual literacy strategies in Indonesian language learning can be an effective solution to overcome the reading interest crisis in primary schools. By integrating visual media into educational practice, educators can create a more engaging and interactive learning environment that promotes literacy development and critical thinking. This approach not only addresses the issue of reading interest but also helps develop students' cognitive and analytical skills, which are essential for academic success and lifelong learning.